Developing a Financial Literacy Program with Survivors of Intimate Partner Violence: The Voices of Survivors. Issue 4 (25th September 2019) - Stylianou, Amanda M; Counselman-Carpenter, Elisabeth; Redcay, Alex
Abstract: As the social work field increasingly recognizes economic abuse within intimate partner relationships, the field has developed financial empowerment programs to empower survivors for their financial future. Although research has demonstrated the effectiveness of financial literacy programs, there are barriers to their implementation in the field. Studies have explored, from the perspective of advocates, best practices in incorporating financial literacy into services; however, no studies have explored implementation approaches from the perspective of survivors. This study explores, from the perspective of 34 survivors, approaches for implementing financial literacy programming. Participants described their understanding of financial empowerment as being in charge of finances, having financial power, and not having to endure the struggle. To counter financial disempowerment, participants identified the need for financial confidence, knowledge, and tools. Participants shared their strategies for saving money, though many participants reported barriers to using banks as savings tools. Almost all participants stressed the importance of financial literacy services for survivors, especially around banking, credit, and debt. Finally, participants shared recommendations for job readiness and training programming. Findings have implications for domestic violence and broader social work organizations implementing financial empowerment services. Social workers can support financial empowerment efforts through program development and research efforts.